2018
DOI: 10.1017/s0950268818000808
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis epidemiology in Argentina: TRENDS after the introduction of maternal immunisation

Abstract: Data on the impact of the recently recommended maternal pertussis vaccination are promising, but still insufficient to universalise this approach. We thus compared the epidemiological data prior to the implementation of this vaccination strategy in Argentina (2012) with the figures reported after 2012. During that 2010-2016 period, two outbreaks occurred, one in 2011 and another in 2016. In the former, the incidence was 6.9/100 000 inhabitants and the case-fatality rate 2.6%. Thereafter, a decline in incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
0
11
0
10
Order By: Relevance
“…Within the current epidemiologic context of pertussis, many countries in which the number of cases have increased in mainly newborns and infants not receiving primary doses because of age (Fabricius et al, 2018;Agrawal et al, 2019) have once again begun discussion on neonatal vaccination and its possible implementation (Lumbreras Areta et al, 2019). Neonatal immunization would provide an early protection for newborns and infants, thus narrowing the critical period of vulnerability intrinsic to routine vaccination schedules that start later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the current epidemiologic context of pertussis, many countries in which the number of cases have increased in mainly newborns and infants not receiving primary doses because of age (Fabricius et al, 2018;Agrawal et al, 2019) have once again begun discussion on neonatal vaccination and its possible implementation (Lumbreras Areta et al, 2019). Neonatal immunization would provide an early protection for newborns and infants, thus narrowing the critical period of vulnerability intrinsic to routine vaccination schedules that start later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Using mice, we detected that pertussis immunization of pregnant females with the acellular vaccine conferred protective immunity that is transferred both transplacentally and via offspring breastfeeding without compromising the protection boostered by subsequent infant vaccination (Gaillard et al, 2017). In humans, extremely significant data recently obtained would support the following statements: (1) human maternal immunization is safe for women and fetuses, (2) maternal-immunization strategy is able to decrease the lethality rates in newborns and infants born to immunized mothers (Fabricius et al, 2018;Gentile et al, 2018) and (3) maternal immunization is highly protective against pertussis, especially in the first 2 months of life, but also up to the first year. Moreover, Baxter et al (2017) found that maternal immunization provided additional protection for infants who received the first dose of pertussis vaccine.…”
Section: Introductionmentioning
confidence: 93%
“…The programme in the United Kingdom is safe and highly effective , with the highest proportional reduction in cases and hospital admissions in infants less than 3 months of age . Maternal pertussis vaccination has been introduced by the United States, Australia, South American and other European countries .…”
Section: Introductionmentioning
confidence: 99%
“…In other countries, the replacement of the whole cell vaccine by acellular vaccines has been considered as a possible cause, due to its shorter immune response [22]. This view can be debated, since the disease also reappeared in countries that used whole cell vaccines, such as Brazil and Argentina [23][24][25].…”
Section: Discussionmentioning
confidence: 99%